m7G-related gene NUDT4 as a novel biomarker promoting cancer cell proliferation in lung adenocarcinoma - Liu, Yafei; Jiang, Bin; Lin, Chunjie; Zhu, Wanyinhui; Chen, Dingrui; Sheng, Yinuo; Lou, Zhiling; Ji, Zhiheng; Wu, Chuanqiang; Wu, Ming (Frontiers in Oncology, 2023)
Background: Lung cancer is a notorious leading cause of cancer patients’ mortality. N7-methylguanosine (m7G) modification as a translational regulation pattern was reported to participate in multiple types of cancer progression, but little is known in lung cancer. This study attempts to explore the role of m7G-related proteins in genetic and epigenetic variations in lung adenocarcinoma, relations with clinical prognosis, immune infiltration, and immunotherapy. Methods: Sequencing data were obtained from the GDC Data Portal and GEO databases. Consensus clustering was utilized to distinguish m7G clusters, responses to immunotherapy were also evaluated. Otherwise, Univariate, multivariate Cox, and LASSO Cox regression analyses were used to screen independent prognostic factors and generated risk scores for constructing a survival prediction model. Multiple cell types proportions such as epithelial cells and immune cells were identified to verify the results in bulk-RNA results. shRNA Tet-on plasmids, CRISPER/Cas9 for konckout plasmids, and NUDT4 over-expression plasmids were constructed to inhibit or promote tumor cell NUDT4 expression, then the RT-qPCR, CCK8 proliferation assay, and transwell assay were used to observe tumor cell biological functions. Results: Fifteen m7G-related genes were highly expressed in tumor samples and twelve genes were associated with poor prognosis. m7G cluster-B had lower immune infiltration level, worse survival, and samples which predicted poor responses to immunotherapy. The Multivariate Cox model figured out that the NUDT4 and WDR4 were independent risk factors. Single-cell m7G GSVA scores also had a negative correlation tendency with immune infiltration level and T cells PD1 expression, but the statistics were not significant. Knocking down as well as knocking out NUDT4 expression significantly inhibited cell proliferation capability in A549 and H1299 cells. On the contrast, over-expressing NUDT4 promoted tumor cell proliferation. But there was no difference in migration capability either in knockdown, knockout, or overexpression groups. Conclusions: Our study revealed that N7-methylguanosine modification-related proteins were closely related to the tumor microenvironment, immune cell infiltration, responses to immunotherapy, and patients’ prognosis in lung adenocarcinoma, and could be a useful biomarker for the identification of patients who will benefit from immunotherapy. m7G modification protein NUDT4 may be a novel biomarker in promoting progression of lung cancer.